2011
DOI: 10.1002/meet.2011.14504801059
|View full text |Cite
|
Sign up to set email alerts
|

Document constancy and persistence: A study of Web pages in library and information science domain

Abstract: A selection of ninety English language library and information science organization Web sites and their associated pages are analyzed. A majority of Web sites are located on the .org generic top-level domain or the country code top-level domain of the country of origin (to include .int). The Web sites and pages were monitored for ninetyone days beginning November 2, 2010. The data suggest that while Web sites may fluctuate in size on a day to day basis, there is a general tendency toward accretion of pages. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Oguz and Koehler () proposed the use of the cosine similarity (Baeza‐Yates & Ribeiro‐Neto, ) to measure change. However, change in web document content may focus on a particular type of content or topic.…”
Section: Changementioning
confidence: 99%
See 1 more Smart Citation
“…Oguz and Koehler () proposed the use of the cosine similarity (Baeza‐Yates & Ribeiro‐Neto, ) to measure change. However, change in web document content may focus on a particular type of content or topic.…”
Section: Changementioning
confidence: 99%
“…Most papers address web document inaccessibility (e.g., Hennessey & Ge, ; Rumsey, ; Russell & Kane, ; Strader & Hamill, ; Taylor & Hudson, ; Tyler & McNeil, ; Wagner, Gebremichael, Taylor, & Soltys, ). Relatively few have been concerned with content changes to those documents (e.g., Bar‐Ilan & Peritz, ; Oguz & Koehler, ; Payne & Thelwall, , , ). This research note reexamines URL data originally identified and collected in 1995 (Koehler, ).…”
Section: Introductionmentioning
confidence: 99%
“…This updated study is important because URL decay continues to be an issue of concern to the scholarly community. Numerous calls to remedy the issue have been made [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], including the original study [1], but little is known about the change in URL decay over time in one specific academic discipline. A review of the literature on URL decay finds that most papers on the topic See end of article for supplemental content.…”
Section: Introductionmentioning
confidence: 99%
“…primarily address URL inaccessibility at one snapshot in time [2][3][4][5][6][7], URL inaccessibility at one snapshot in time for a specific discipline (i.e., computer science, information science) [8][9] or a specific journal (i.e., American Political Science Review, Journal of the Medical Library Association) [10][11]. A smaller number of studies have looked at content changes in a sample of URLs [12][13][14][15][16], but no other studies known to the authors of this study have followed a similar methodology to this study by comparing data from a specific discipline over two distinct time periods. For this reason, this study offers a unique perspective on the literature of URL decay.…”
Section: Introductionmentioning
confidence: 99%